شروط الواقف في دولة ماليزيا: دراسة تحليلية في ضوء مقاصد الوقف - Ab Rahman, M. F.; Abdullah Thaidi, H.; Azeemi, Ab Rahman, A.; Ab Rahim, S. F. (Universiti Sains Islam Malaysia, 2024)
This paper aims to critically examine the legal provisions relating to the terms set forth by the waqif (donor) in the waqf enactments in Malaysia and the extent to which the waqif could possibly set terms and conditions of the waqf. These terms could include the selection of beneficiaries, stipulations governing the appointment of the mutawalli (waqf manager) and the distribution of waqf income. A qualitative methods have been employed to analyse the data through inductive, deductive and comparative approaches. The findings show that there are avenues in waqf enactments in Malaysia to allow the provision any conditions provided that is consented by the Waqf Management. Thus, this paper recommends that the Waqf Corporations and Islamic Religious Councils in every states in Malaysia should revisit the existing rulings and legal framework of waqf in order to harmonise these with the purposes of waqf for the benefit of waqif, waqf properties and beneficiaries.